2009
DOI: 10.1186/1743-0003-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in neurological disorders and challenges for noninvasive brain stimulation (NBS)

Abstract: There has been considerable interest in trialing NBS in a range of neurological conditions, and in parallel the range of NBS techniques available continues to expand. Underpinning this is the idea that NBS modulates neuroplasticity and that plasticity is an important contributor to functional recovery after brain injury and to the pathophysiology of neurological disorders. However while the evidence for neuroplasticity and its varied mechanisms is strong, the relationship to functional outcome is less clear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…While neural plasticity contributes significantly to functional recovery, it should be noted that not all types are beneficial. For example, maladaptive plasticity and inappropriate axonal sprouting can lead to spasticity, pathological pain, schizophrenia, and seizures (Dimitrijevi and Nathan, 1967; Flor et al, 1995; Teyler et al, 2001; Quartarone et al, 2008; Thickbroom and Mastaglia, 2009; Kuner, 2010; Hasan et al, 2011). …”
Section: The Physiology Of Recovery From Neurological Injurymentioning
confidence: 99%
“…While neural plasticity contributes significantly to functional recovery, it should be noted that not all types are beneficial. For example, maladaptive plasticity and inappropriate axonal sprouting can lead to spasticity, pathological pain, schizophrenia, and seizures (Dimitrijevi and Nathan, 1967; Flor et al, 1995; Teyler et al, 2001; Quartarone et al, 2008; Thickbroom and Mastaglia, 2009; Kuner, 2010; Hasan et al, 2011). …”
Section: The Physiology Of Recovery From Neurological Injurymentioning
confidence: 99%
“…Brain plasticity may be neuronal or nonneuronal, and the former may be synaptic or non‐synaptic (37). Thus, modulation of synaptic transmission (38) is only one of many mechanisms of brain plasticity (39).…”
Section: Subacute and Chronic Changes After Tbimentioning
confidence: 99%
“…Other variables, such as intensity of current, stimulated area, stimulation time and methods used to measure the outcomes were similar, corroborating with protocols used by other authors in different populations that investigated the same outcomes (19,20) . It is known that after stroke may occur a change in synaptic homeostasis, which affects individuals' cognition (21) . In the present study the verbal and visual WM showed significant improvements after the use of tDCS, supporting the results found in diverse population by other authors (22,23) .…”
Section: Discussionmentioning
confidence: 99%